Health savings accounts for small businesses and entrepreneurs: Shopping, take-up and implementation challenges - Susan M. Gates; Pinar Karaca-Mandic; James R. Burgdorf; Kanika Kapur (University College Dublin, UCD School of Economics, 2009)
A combination of high deductible health plans (HDHPs) and health savings accounts (HSAs) holds promise for expanding health insurance for small firms. We provide information on HSA take-up and shopping behavior from a 2008 survey of female small business owners, revealing that the HSA marketplace can be confusing for small firms. HSAs may have expanded access to health insurance for the smallest firms (under three employees), but not for small firms more generally. A sizable number of firms offering HSA-eligible insurance did not offer attached HSAs. Firms offering HSAs were satisfied with their experiences, but faced challenges in implementing them.
hdl:10197/2623
Keywords: 330